Examining the Potential of the Super Dual Auroral Radar Network for Monitoring the Space Weather Impact of Solar X‐Ray Flares. Issue 9 (12th September 2018) - Fiori, R. A. D.; Koustov, A. V.; Chakraborty, S.; Ruohoniemi, J. M.; Danskin, D. W.; Boteler, D. H.; Shepherd, S. G.
Abstract: Increased electron density in the ionosphere due to photoionization by radiation emitted during a solar X‐ray flare impacts high‐frequency (HF) radio wave propagation. Shortwave fadeout (SWF) due to the enhanced D region absorption that results is characterized by the level of cosmic radio noise attenuation derived from riometer measurements. SWF impacts HF radio propagation and has been identified in the Super Dual Auroral Radar Network (SuperDARN) data. An X2.1 solar X‐ray flare that erupted on 11 March 2015 is examined to determine its effects on HF radio propagation. Riometer data indicate a sharp enhancement in absorption, which falls off with increasing solar zenith angle. SuperDARN radars observed a suppression of both ground scatter and ionospheric echoes. Ground scatter data indicated a rapid weakening of signal from far to near ranges followed by a ~20‐min interval of complete signal loss. Recovery lasted ~30 min and proceeded from near to far ranges. Prior to the complete signal loss, an apparent sharp velocity impulse (Doppler flash) lasting 1–2 min was observed in the ground scatter data. The peak of this flash preceded the onset of enhanced absorption. The onset of signal loss by SuperDARN preceded the onset of enhanced absorption observed by riometers. Both data sets observed a positive correlation between increasing delay in onset and increasing solar zenith angle with onset progressing at an average rate of 16.7°/min (0.060 min/°). Agreement between riometer and SuperDARN indicates the possibility of using a joint data set for improved monitoring of the space weather impact of solar X‐ray flares. Key Points: Solar X‐ray flares may impact HF radio wave propagation on the dayside, to which riometers and SuperDARN radars are sensitive Riometer and SuperDARN instruments demonstrate a solar zenith angle dependence on the onset time of the observed response to the solar X‐ray flare A velocity impulse observed by SuperDARN radars prior to complete signal loss may serve as a warning that shortwave fadeout is imminent